Educational games in physical education to increase self-confidenceChildren with Special Needs in Padang Special School Perwari - Tri Rafi Harma; Eddy Marheni; Eko Purnomo (Fakultas Ilmu Pendidikan)
This research is based on the problem of trust in children with special needs. Learning development methods are not only in the classroom, can also be done outside the classroom. The purpose of this study is to provide solutions in solving problems of more effective learning planning systems in educational games in the field. This research was conducted on August 3 - September 28, 2018 at the Perwari Padang, Perwari. The focus of the research is on game modification learning that has been conducted at Padang Perwari school. This type of research is qualitative research with the observation method, the education educative game program, and documentation. The main object in this study is students with special needs in Padang Perwari. The results of research on good social interaction, the emergence of cooperation in completing a game, and the growth of confidence in interacting with friends in completing physical activities.